Coevolution of species in competition: A Theoretical Study. - Matesi, C.; Jayakar, S.D
A model is presented for the coevolution of several species in competition, each species being genetically variable at one locus with respect to this competition. A function was found that is maximized during coevolution. This maximization principle was used in order to study the result of competition for a single resource on the utilization functions of the species competing for that resource. In particular, the conditions under which ecologicalcharacter displacement can evolve were examined.
Keywords: COEVOLUTION; SPECIES; COMPETITION; EVOLVE